Conformal bubbler cooling for molds by metal deposition process. (December 2015) - Eiamsa-ard, Kunnayut; Wannissorn, Kittinat
Abstract: Molds with conformal bubbler cooling channels have been developed in order to reduce the cycle time of the plastic injection process, which in turn has increased the production rate. In addition, part warpage can be greatly reduced in the injection process because the temperature distribution is uniform over the mold surfaces. Molds with conformal cooling designs, however, are still limited to computer simulations for generating the cooling channels or calculating the cooling rates[1–4] . This is mainly because there is "virtually" no fabrication technique that can effectively make the complicated conformal cooling channels. Even though metal deposition processes have the potential to create such complex mold shapes, most of the metal deposition processes are still in the developmental stage in laboratories. Molds formed by some of the metal deposition processes are not suitable for real industry use because the costs are still too expensive. This paper describes how to create a mold with conformal bubbler cooling tunnels through a metal deposition process that can actually be used in plastic injection industries. Experiments are conducted to confirm the normal temperature distribution over the mold surfaces. Highlights: Mold design with conformal cooling have been developed. Simulations have been done to make mold hollow but strong enough for all forces. Manufacturability is tested using metal deposition technique. Temperature distributions are uniform over the mold surfaces from the tests.